High-strength permeable asphalt concrete and preparation method thereof
By adding exothermic coarse aggregate and exothermic filler to asphalt concrete, the heat released by electrochemical corrosion and hydration reaction is used to melt salt crystals, keeping the pores open. This solves the problem of reduced permeability in salt spray environments and improves the safety and service life of roads.
Patent Information
- Application Number
- CN202510626311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-11-14
AI Technical Summary
When existing asphalt concrete is used on salt fog coastal highways, salt crystals block the pores, leading to a decrease in permeability and affecting road safety.
The combination of exothermic coarse aggregate and exothermic filler releases heat through electrochemical corrosion and hydration reactions, melts salt crystals, keeps pores open, and continuously provides heat through a slow-release mechanism to promote water penetration.
It improves the permeability of asphalt concrete in salt spray environments, reduces driving safety hazards, and enhances road safety and lifespan.
Smart Images

Figure BDA0005404048210000111
Abstract
Description
Technical Field
[0001] This invention relates to the field of engineering materials technology, specifically to a high-strength permeable asphalt concrete and its preparation method. Background Technology
[0002] Asphalt concrete is a composite material made by mixing asphalt, coarse and fine aggregates (crushed stone, sand), mineral fillers (such as mineral powder), and additives at high temperatures. It has high strength, durability, and good skid resistance. According to the type of mixture, it can be divided into continuous gradation, asphalt mastic, open gradation, etc., and is suitable for different road requirements. Construction requires mixing, transportation, paving, and compaction. Temperature control is the key. It is widely used in highways, airport runways, etc., and combines driving comfort and economy, but regular maintenance is required to prevent rutting, cracks and other defects.
[0003] In the prior art, when asphalt concrete is used in salt fog coastal highways, it will be in a salt fog environment for a long time. The sodium chloride and other salts in the salt fog will seep into the interior of the asphalt mixture with the water. After the water evaporates, the salt will crystallize and gradually block the interconnected pores of the asphalt concrete, hindering the water infiltration path, resulting in poor drainage, easy water accumulation, and affecting road driving safety. Based on this, the present invention provides a high-strength permeable asphalt concrete and its preparation method. Summary of the Invention
[0004] The purpose of this invention is to provide a high-strength permeable asphalt concrete and its preparation method to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing high-strength permeable asphalt concrete, comprising the following raw materials in parts by weight: 55-65 parts coarse aggregate, 15-25 parts fine aggregate, 5-10 parts exothermic coarse aggregate, 4-8 parts exothermic filler, 4-8 parts asphalt, 3-6 parts mineral filler, 2-5 parts additives, 1-3 parts water, and 0.5-1.5 parts solvent.
[0006] Preferably, the method for preparing the exothermic packing includes the following steps:
[0007] Step 1, Raw material mixing: Select nano calcium oxide and silica sol and mix them at a mass ratio of 3:1. Then add them to a ball mill and grind for 30-60 minutes to obtain the first mixture.
[0008] Step 2, Microsphere Forming: The first mixture is atomized and dried by spray dryer, and then sieved to obtain porous ceramic microspheres;
[0009] Step 3, Surface modification: Soak porous ceramic microspheres in silane coupling agent solution for 30-60 min, then transfer them to centrifuge and centrifuge at 3000-5000 rpm for 5-10 min. Take the first precipitate and transfer it to an oven to dry at 50-80℃ for 1-2 h to obtain quicklime slow-release microspheres, which are exothermic fillers.
[0010] Preferably, in step 1, the particle size of the nano-calcium oxide is 50-100 nm, the silica content in the silica sol is 20-30%, in step 2 the spray dryer is set with an inlet temperature of 180-220℃, an outlet temperature of 80-100℃, and a screen aperture of 2-5 mm, and in step 3 the mass ratio of porous ceramic microspheres to silane coupling agent solution is 1:(3-5).
[0011] Preferably, the method for preparing the exothermic coarse aggregate includes the following steps:
[0012] Step 1: Aggregate pretreatment: Select volcanic rock crushed and ground to a particle size of 5-10 mm as raw material. Use plasma equipment at 50-100W to treat the surface of the volcanic rock for 5-10 minutes, then soak it in hydrochloric acid solution for 2-4 hours, wash it with water until neutral, and then dry it to obtain pretreated aggregate.
[0013] Step 2, Iron powder loading: Immerse the pretreated aggregate in ferric chloride solution, add sodium borohydride and sodium molybdate accounting for 0.05-0.1% of the mass of ferric chloride, stir and react for 1-2 hours, then transfer to a centrifuge, centrifuge at 2000-4000 rpm for 5-10 minutes, and take the second precipitate to obtain the prepared aggregate;
[0014] Step 3, salt fixation: Spray a sodium chloride-polyvinyl alcohol mixture onto the aggregate to be prepared, and dry it at 60-80℃ to obtain iron powder composite oxide aggregate, which is exothermic coarse aggregate.
[0015] Preferably, in step one, the concentration of hydrochloric acid solution is 5-10%, and the mass ratio of volcanic rock to hydrochloric acid solution is 1:(3-5); in step two, the concentration of ferric chloride solution is 10-20%, the mass ratio of pretreated aggregate to ferric chloride solution is 1:(2-4), and the molar ratio of ferric chloride to sodium borohydride is 1:2; in step three, the concentration of sodium chloride in the sodium chloride-polyvinyl alcohol mixture is 5-10%, and the concentration of polyvinyl alcohol is 1-3%.
[0016] Preferably, the silica sol in step 1 contains 0.1-0.5% nano-titanium dioxide by total mass of silica sol.
[0017] Preferably, in step 3, the concentration of the silane coupling agent solution is 2-4%, and the silane coupling agent solution is prepared by mixing KH-550 and anhydrous ethanol at a volume ratio of 1:(3-5).
[0018] Preferably, the asphalt can be selected from any one of SBS modified asphalt, ethylene-vinyl acetate polymer modified asphalt, and styrene-butadiene rubber modified asphalt; the additive can be selected from any one of SBS, SBR, and EVA; and the solvent can be selected from any one of KH-550, KH-560, and KH-570.
[0019] Preferably, the mineral filler is prepared by mixing limestone powder and silica fume at a mass ratio of (2-4):1, wherein the calcium carbonate content of the limestone powder is ≥90% and the fineness is 200-400 mesh, and the silica fume has a silicon dioxide content of ≥90%.
[0020] Preferably, a method for preparing high-strength permeable asphalt concrete includes the following steps:
[0021] S1. Heat the coarse aggregate, fine aggregate, and exothermic coarse aggregate to 150-170℃ to obtain preheated aggregate;
[0022] S2. Heat the asphalt to 160-180℃, add mineral filler, exothermic filler, additives and water, and stir at 30-80 rpm for 30-60 minutes to obtain asphalt mixture.
[0023] S3. Spray the solvent evenly onto the surface of the preheated aggregate and let it stand for 10-20 minutes to obtain the prepared aggregate.
[0024] S4. Add the prepared aggregate and asphalt mixture to a twin-shaft mixer and mix at a mixing speed of 30-50 rpm for 5-10 minutes to obtain the prepared material.
[0025] S5. Pour the prepared material into the mold, compact it under 8-12MPa conditions, and then demold it after it cools naturally to room temperature to obtain high-strength permeable asphalt concrete.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] 1. In this preparation method, when asphalt concrete with added exothermic coarse aggregate and exothermic filler is used on salt spray coastal highways, the sodium chloride and water vapor in the salt spray form an electrolyte solution. After contacting the iron powder in the exothermic coarse aggregate, an electrochemical corrosion reaction occurs. During this process, the iron powder loses electrons and is oxidized, releasing heat. At the same time, the moisture in the salt spray and the quicklime in the exothermic filler undergo a hydration reaction, releasing a large amount of heat. The two work together to melt the salt crystals in the concrete pores under long-term salt spray conditions, keeping the pores open. At the same time, this heat increases the fluidity of water, allowing it to penetrate into the internal pores of the concrete more quickly. This improves the permeability of asphalt concrete in long-term salt spray environments, effectively solving the problem of decreased permeability caused by salt crystal blockage of pores on salt spray coastal highways. This ensures that the road surface has good drainage capacity and maintains the long-term effectiveness of permeability.
[0028] 2. In this preparation method, the electrochemical corrosion reaction of the exothermic coarse aggregate and the hydration reaction of the exothermic filler continuously release heat, which accelerates the evaporation rate of water. At the same time, the heat reduces the viscosity of water, making the water flow more smoothly and penetrate into the pores inside the concrete more quickly, rather than accumulating on the surface. The formation of a water film requires the continuous accumulation of water on the surface. However, the rapid evaporation and infiltration of water here makes it difficult to form a continuous water film. Even if it is formed briefly, it will dissipate rapidly due to the heat. This solves the driving safety hazard caused by water film on the salt fog coastal highway, reduces the risk of vehicle skidding and loss of control, and improves the safety of road use. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1: This example provides a method for preparing high-strength permeable asphalt concrete, comprising the following raw materials by weight: 55 parts coarse aggregate, 15 parts fine aggregate, 5 parts exothermic coarse aggregate, 4 parts exothermic filler, 4 parts asphalt, 3 parts mineral filler, 2 parts additives, 1 part water, and 0.5 parts solvent.
[0031] The preparation method of the exothermic packing includes the following steps:
[0032] Step 1, Raw material mixing: Select nano calcium oxide and silica sol and mix them at a mass ratio of 3:1. Then add them to a ball mill and grind for 30 minutes to obtain the first mixture.
[0033] Step 2, Microsphere Forming: The first mixture is atomized and dried by spray dryer, and then sieved to obtain porous ceramic microspheres;
[0034] Step 3, Surface modification: Soak porous ceramic microspheres in silane coupling agent solution for 30 min, then transfer them to centrifuge and centrifuge at 3000 rpm for 5 min. Take the first precipitate and transfer it to an oven to dry at 50℃ for 1 h to obtain quicklime slow-release microspheres, which are exothermic fillers.
[0035] In step 1, the particle size of the nano-calcium oxide is 50 nm, the silica content in the silica sol is 20%, in step 2 the spray dryer is set with an inlet temperature of 180°C, an outlet temperature of 80°C, and a screen aperture of 2 mm, and in step 3 the mass ratio of porous ceramic microspheres to silane coupling agent solution is 1:3.
[0036] The method for preparing exothermic coarse aggregate includes the following steps:
[0037] Step 1: Aggregate pretreatment: Select volcanic rock crushed and ground to a particle size of 5mm as raw material, use plasma equipment to treat the surface of volcanic rock at 50W for 5 minutes, then soak it in hydrochloric acid solution for 2 hours, then wash it with water until neutral and dry it to obtain pretreated aggregate;
[0038] Step 2, Iron powder loading: The pretreated aggregate is immersed in ferric chloride solution, sodium borohydride and sodium molybdate accounting for 0.05% of the mass of ferric chloride are added, and the mixture is stirred and reacted for 1 hour. Then it is transferred to a centrifuge and centrifuged at 2000 rpm for 5 minutes. The second precipitate is then taken to obtain the prepared aggregate.
[0039] Step 3, salt fixation: Spray a sodium chloride-polyvinyl alcohol mixture onto the aggregate to be prepared, and dry it at 60°C to obtain iron powder composite oxide aggregate, which is exothermic coarse aggregate.
[0040] In step one, the concentration of hydrochloric acid solution is 5%, and the mass ratio of volcanic rock to hydrochloric acid solution is 1:3. In step two, the concentration of ferric chloride solution is 10%, the mass ratio of pretreated aggregate to ferric chloride solution is 1:2, and the molar ratio of ferric chloride to sodium borohydride is 1:2. In step three, the concentration of sodium chloride in the sodium chloride-polyvinyl alcohol mixture is 5%, and the concentration of polyvinyl alcohol is 1%.
[0041] In step 1, the silica sol contains 0.1% nano-titanium dioxide by mass of the total silica sol.
[0042] In step 3, the concentration of the silane coupling agent solution is 2%, and the silane coupling agent solution is prepared by mixing KH-550 and anhydrous ethanol at a volume ratio of 1:3.
[0043] The asphalt selected is SBS modified asphalt, the additive is SBS, and the solvent is KH-550.
[0044] The mineral filler is prepared by mixing limestone powder and silica fume at a mass ratio of 2:1. The limestone powder has a calcium carbonate content of ≥90% and a fineness of 200 mesh, while the silica fume has a silicon dioxide content of ≥90%.
[0045] One method for preparing high-strength permeable asphalt concrete includes the following steps:
[0046] S1. Heat the coarse aggregate, fine aggregate, and exothermic coarse aggregate to 150°C to obtain preheated aggregate;
[0047] S2. Heat the asphalt to 160℃, add mineral filler, exothermic filler, additives and water, and stir at 30 rpm for 30 minutes to obtain asphalt mixture.
[0048] S3. Spray the solvent evenly onto the surface of the preheated aggregate and let it stand for 10 minutes to obtain the prepared aggregate;
[0049] S4. Add the prepared aggregate and asphalt mixture to a twin-shaft mixer and mix at 30 rpm for 5 minutes to obtain the prepared material.
[0050] S5. Pour the prepared material into the mold, compact it under 8MPa conditions, and then demold it after it cools naturally to room temperature to obtain high-strength permeable asphalt concrete.
[0051] Example 2, a method for preparing high-strength permeable asphalt concrete, comprising the following raw materials in parts by weight: 65 parts coarse aggregate, 25 parts fine aggregate, 10 parts exothermic coarse aggregate, 8 parts exothermic filler, 8 parts asphalt, 6 parts mineral filler, 5 parts additives, 3 parts water, and 1.5 parts solvent.
[0052] The preparation method of the exothermic packing includes the following steps:
[0053] Step 1, Raw material mixing: Select nano calcium oxide and silica sol and mix them at a mass ratio of 3:1. Then add them to a ball mill and grind for 60 minutes to obtain the first mixture.
[0054] Step 2, Microsphere Forming: The first mixture is atomized and dried by spray dryer, and then sieved to obtain porous ceramic microspheres;
[0055] Step 3, Surface modification: Soak porous ceramic microspheres in silane coupling agent solution for 60 min, then transfer them to centrifuge and centrifuge at 5000 rpm for 10 min. Take the first precipitate and transfer it to an oven to dry at 80℃ for 2 h to obtain quicklime slow-release microspheres, which are exothermic fillers.
[0056] In step 1, the particle size of the nano-calcium oxide is 100nm, the silica content in the silica sol is 30%, in step 2 the spray dryer is set with an inlet temperature of 220℃, an outlet temperature of 100℃, and a screen aperture of 5mm, and in step 3 the mass ratio of porous ceramic microspheres to silane coupling agent solution is 1:5.
[0057] The method for preparing exothermic coarse aggregate includes the following steps:
[0058] Step 1: Aggregate pretreatment: Select volcanic rock crushed and ground to a particle size of 10mm as raw material, use plasma equipment to treat the surface of volcanic rock at 100W for 10 minutes, then soak it in hydrochloric acid solution for 4 hours, then wash it with water until neutral and dry it to obtain pretreated aggregate.
[0059] Step 2, Iron powder loading: The pretreated aggregate is immersed in ferric chloride solution, sodium borohydride and sodium molybdate accounting for 0.1% of the mass of ferric chloride are added, and the mixture is stirred and reacted for 2 hours. Then it is transferred to a centrifuge and centrifuged at 4000 rpm for 10 minutes. The second precipitate is then taken to obtain the prepared aggregate.
[0060] Step 3, salt fixation: Spray a sodium chloride-polyvinyl alcohol mixture onto the aggregate to be prepared, and dry it at 80°C to obtain iron powder composite oxide aggregate, which is exothermic coarse aggregate.
[0061] In step one, the concentration of hydrochloric acid solution is 10%, and the mass ratio of volcanic rock to hydrochloric acid solution is 1:5. In step two, the concentration of ferric chloride solution is 20%, the mass ratio of pretreated aggregate to ferric chloride solution is 1:4, and the molar ratio of ferric chloride to sodium borohydride is 1:2. In step three, the concentration of sodium chloride in the sodium chloride-polyvinyl alcohol mixture is 10%, and the concentration of polyvinyl alcohol is 3%.
[0062] In step 1, the silica sol contains 0.5% nano-titanium dioxide by mass of the total silica sol.
[0063] In step 3, the concentration of the silane coupling agent solution is 4%, and the silane coupling agent solution is prepared by mixing KH-550 and anhydrous ethanol at a volume ratio of 1:5.
[0064] The asphalt selected is styrene-butadiene rubber modified asphalt, the additive is EVA, and the solvent is KH-570.
[0065] The mineral filler is prepared by mixing limestone powder and silica fume at a mass ratio of 4:1. The limestone powder has a calcium carbonate content of ≥90% and a fineness of 400 mesh, while the silica fume has a silicon dioxide content of ≥90%.
[0066] One method for preparing high-strength permeable asphalt concrete includes the following steps:
[0067] S1. Heat the coarse aggregate, fine aggregate, and exothermic coarse aggregate to 170°C to obtain preheated aggregate;
[0068] S2. Heat the asphalt to 180°C, add mineral filler, exothermic filler, additives and water, and stir at 80 rpm for 60 minutes to obtain asphalt mixture.
[0069] S3. Spray the solvent evenly onto the surface of the preheated aggregate and let it stand for 20 minutes to obtain the prepared aggregate;
[0070] S4. Add the prepared aggregate and asphalt mixture to a twin-shaft mixer and mix at 50 rpm for 10 min to obtain the prepared material.
[0071] S5. Pour the prepared material into the mold, compact it under 12MPa conditions, and then demold it after it cools naturally to room temperature to obtain high-strength permeable asphalt concrete.
[0072] Example 3: A method for preparing high-strength permeable asphalt concrete, comprising the following raw materials in parts by weight: 60 parts coarse aggregate, 20 parts fine aggregate, 8 parts exothermic coarse aggregate, 6 parts exothermic filler, 6 parts asphalt, 4 parts mineral filler, 3 parts additives, 2 parts water, and 1 part solvent.
[0073] The preparation method of the exothermic packing includes the following steps:
[0074] Step 1, Raw material mixing: Select nano calcium oxide and silica sol and mix them at a mass ratio of 3:1. Then add them to a ball mill and grind for 45 minutes to obtain the first mixture.
[0075] Step 2, Microsphere Forming: The first mixture is atomized and dried by spray dryer, and then sieved to obtain porous ceramic microspheres;
[0076] Step 3, Surface modification: The porous ceramic microspheres were soaked in a silane coupling agent solution for 45 min, then transferred to a centrifuge and centrifuged at 4000 rpm for 8 min. The first precipitate was then taken and transferred to an oven and dried at 60℃ for 1.5 h to obtain quicklime slow-release microspheres, which are the exothermic fillers.
[0077] In step 1, the particle size of the nano-calcium oxide is 80nm, the silica content in the silica sol is 25%, in step 2 the spray dryer is set with an inlet temperature of 200℃, an outlet temperature of 90℃, and a screen aperture of 4mm, and in step 3 the mass ratio of porous ceramic microspheres to silane coupling agent solution is 1:4.
[0078] The method for preparing exothermic coarse aggregate includes the following steps:
[0079] Step 1: Aggregate pretreatment: Select volcanic rock crushed and ground to a particle size of 8mm as raw material, use plasma equipment to treat the surface of volcanic rock at 80W for 8 minutes, then soak it in hydrochloric acid solution for 3 hours, then wash it with water until neutral and dry it to obtain pretreated aggregate;
[0080] Step 2, Iron powder loading: The pretreated aggregate is immersed in ferric chloride solution, sodium borohydride and sodium molybdate accounting for 0.08% of the mass of ferric chloride are added, and the mixture is stirred and reacted for 1.5 hours. Then it is transferred to a centrifuge and centrifuged at 3000 rpm for 8 minutes. The second precipitate is then taken to obtain the prepared aggregate.
[0081] Step 3, salt fixation: Spray a sodium chloride-polyvinyl alcohol mixture onto the aggregate to be prepared, and dry it at 70°C to obtain iron powder composite oxide aggregate, which is exothermic coarse aggregate.
[0082] In step one, the concentration of hydrochloric acid solution is 8%, and the mass ratio of volcanic rock to hydrochloric acid solution is 1:4. In step two, the concentration of ferric chloride solution is 15%, the mass ratio of pretreated aggregate to ferric chloride solution is 1:3, and the molar ratio of ferric chloride to sodium borohydride is 1:2. In step three, the concentration of sodium chloride in the sodium chloride-polyvinyl alcohol mixture is 8%, and the concentration of polyvinyl alcohol is 2%.
[0083] In step 1, the silica sol contains 0.3% nano-titanium dioxide by mass of the total silica sol.
[0084] In step 3, the concentration of the silane coupling agent solution is 3%, and the silane coupling agent solution is prepared by mixing KH-550 and anhydrous ethanol at a volume ratio of 1:4.
[0085] The asphalt selected is ethylene-vinyl acetate polymer modified asphalt, the additive is SBR, and the solvent is KH-560.
[0086] The mineral filler is prepared by mixing limestone powder and silica fume in a mass ratio of 3:1. The limestone powder has a calcium carbonate content of ≥90% and a fineness of 3000 mesh, while the silica fume has a silicon dioxide content of ≥90%.
[0087] One method for preparing high-strength permeable asphalt concrete includes the following steps:
[0088] S1. Heat the coarse aggregate, fine aggregate, and exothermic coarse aggregate to 160°C to obtain preheated aggregate;
[0089] S2. Heat the asphalt to 170℃, add mineral filler, exothermic filler, additives and water, and stir at 60rpm for 45min to obtain asphalt mixture.
[0090] S3. Spray the solvent evenly onto the surface of the preheated aggregate and let it stand for 15 minutes to obtain the prepared aggregate;
[0091] S4. Add the prepared aggregate and asphalt mixture to a twin-shaft mixer and mix at 45 rpm for 8 minutes to obtain the prepared material.
[0092] S5. Pour the prepared material into the mold, compact it under 10MPa conditions, and then demold it after it cools naturally to room temperature to obtain high-strength permeable asphalt concrete.
[0093] Comparative Example 1: The difference between this comparative example and Examples 1-3 is that no exothermic coarse aggregate is added during the preparation of high-strength permeable asphalt concrete in this comparative example.
[0094] Comparative Example 2 differs from Examples 1-3 in that no exothermic filler is added during the preparation of high-strength permeable asphalt concrete in this comparative example.
[0095] Comparative Example 3 differs from Examples 1-3 in that no exothermic coarse aggregate or exothermic filler is added during the preparation of high-strength permeable asphalt concrete in this comparative example.
[0096] Permeability performance test: Refer to the Technical Specification for Permeable Asphalt Pavement CJJ / T190-2012;
[0097] Water film state test under salt spray environment: The samples were tested using a salt spray chamber (5% NaCl solution, 35℃, continuous spray). After a simulated period of 100 days, the samples were removed and manually sprayed with 300 mL / m³ of water. 2 Simulate heavy rain and record the water film formation time (the time from the start of spraying to the appearance of a continuous water film on the surface) and the dissipation time;
[0098] Strength test under long-term salt spray environment: The sample after 100 days of simulated salt spray environment is tested according to GB / T50081-2019 standard, and the compressive strength retention rate under long-term salt spray environment is calculated according to (strength after aging / initial strength) × 100% = strength retention rate (%).
[0099] Performance testing: The epoxy resin composites prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing, and the test data are recorded in the table below:
[0100]
[0101] Analysis of the data in the comparison table shows that, compared with Examples 1-3, Comparative Example 1 (lacking exothermic coarse aggregate) and Comparative Example 2 (lacking exothermic filler) have poorer permeability, faster water film formation time, and longer water film dissipation time. At the same time, the strength retention rate decreases in the long-term salt spray erosion environment. Meanwhile, Comparative Example 3 (lacking both exothermic coarse aggregate and exothermic filler) shows a significant decrease in all its properties. This indicates that the asphalt concrete prepared by the preparation methods of Examples 1-3 can effectively meet the requirements for use on salt spray coastal highways.
[0102] Further analysis reveals that, in terms of permeability, the exothermic coarse aggregate contains iron powder. In a salt spray environment, sodium chloride and water vapor in the salt spray form an electrolyte solution, which reacts with the iron powder in an electrochemical corrosion reaction. During this process, the iron powder loses electrons and is oxidized, releasing heat. Simultaneously, the exothermic filler contains quicklime, which reacts with the moisture in the salt spray, releasing a large amount of heat through a hydration reaction. The combined effect of these two substances can dissolve the "blockages" formed by salt crystallization in the concrete pores under long-term salt spray conditions, keeping the pores open. At the same time, this heat increases the fluidity of water, allowing it to penetrate the internal pores of the concrete more quickly, thus significantly improving the permeability coefficient.
[0103] Regarding the water film phenomenon, the electrochemical corrosion reaction of exothermic coarse aggregate and the hydration reaction of exothermic filler continuously release heat. This heat causes the surface temperature of concrete to rise, which accelerates the evaporation rate of water. At the same time, the heat reduces the viscosity of water, making the water flow more smoothly and penetrate into the pores inside the concrete more quickly, rather than lingering and accumulating on the surface. The formation of a water film requires the continuous accumulation of water on the surface, but the rapid evaporation and infiltration of water here makes it difficult to form a continuous water film. Even if it forms briefly, it will dissipate rapidly due to the heat.
[0104] Furthermore, the exothermic coarse aggregate loaded with iron powder and sprayed with a sodium chloride-polyvinyl alcohol solution, along with the slow-release structure formed by the polyvinyl alcohol, ensures that the iron powder does not react instantly, but rather reacts slowly with the continuous intrusion of salt spray. This ensures that, under long-term salt spray conditions, the iron powder continuously reacts with the moisture and salt in the salt spray, continuously generating heat to melt salt crystals, maintaining the unobstructed pores of the concrete, preventing blockage, and thus playing a long-term role. Meanwhile, the quicklime in the exothermic filler uses porous ceramic microspheres as a slow-release carrier, slowing down the reaction rate between quicklime and water. When moisture from the salt spray penetrates, the quicklime within the microspheres gradually hydrates and releases heat, rather than reacting rapidly and completely. This slow-release mechanism enables the exothermic filler to continuously interact with infiltrated water in a long-term humid salt spray environment, improving water flow and promoting infiltration. Therefore, through the slow-release regulation of the reaction of iron powder by polyvinyl alcohol and the delaying effect of the reaction of quicklime by porous ceramic microspheres, the exothermic coarse aggregate and exothermic filler can continuously and stably release heat and resist salt crystal blockage and water erosion in the long-term complex environment of the salt spray coastal highway. This ensures the long-term effectiveness of the permeability, strength and other properties of the concrete structure, solves the problem of rapid performance degradation of traditional permeable asphalt concrete due to salt spray erosion, and extends the service life and maintenance cycle of the highway.
[0105] Regarding the retention rate of compressive strength, exothermic coarse aggregates generate ferric hydroxide during electrochemical corrosion reactions. These substances act as "fillers," filling the tiny cracks inside the concrete and enhancing the density of the structure. Exothermic fillers generate cementitious substances such as calcium hydroxide during hydration reactions. These substances form a strong bond with other components in the concrete. In the salt spray coastal highway environment, salt and moisture continuously erode the concrete, and the substances generated by these reactions act as "protective armor," resisting the damage of salt to the internal structure of the concrete and preventing the failure of interfacial bonding caused by deep water erosion. The two work together to reinforce the concrete structure, thus effectively retaining the compressive strength.
[0106] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0107] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing high-strength permeable asphalt concrete, characterized in that, The raw materials include the following parts by weight: 55-65 parts coarse aggregate, 15-25 parts fine aggregate, 5-10 parts exothermic coarse aggregate, 4-8 parts exothermic filler, 4-8 parts asphalt, 3-6 parts mineral filler, 2-5 parts additives, 1-3 parts water, and 0.5-1.5 parts solvent.
2. The method for preparing high-strength permeable asphalt concrete according to claim 1, characterized in that, The method for preparing the exothermic packing includes the following steps: Step 1, Raw material mixing: Select nano calcium oxide and silica sol and mix them at a mass ratio of 3:
1. Then add them to a ball mill and grind for 30-60 minutes to obtain the first mixture. Step 2, Microsphere Forming: The first mixture is atomized and dried by spray dryer, and then sieved to obtain porous ceramic microspheres; Step 3, Surface modification: Soak porous ceramic microspheres in silane coupling agent solution for 30-60 min, then transfer them to centrifuge and centrifuge at 3000-5000 rpm for 5-10 min. Take the first precipitate and transfer it to an oven to dry at 50-80℃ for 1-2 h to obtain quicklime slow-release microspheres, which are exothermic fillers.
3. The method for preparing high-strength permeable asphalt concrete according to claim 2, characterized in that, In step 1, the particle size of the nano-calcium oxide is 50-100nm, the silica content in the silica sol is 20-30%, in step 2 the spray dryer is set with an inlet temperature of 180-220℃, an outlet temperature of 80-100℃, and a screen aperture of 2-5mm, and in step 3 the mass ratio of porous ceramic microspheres to silane coupling agent solution is 1:(3-5).
4. The method for preparing high-strength permeable asphalt concrete according to claim 1, characterized in that, The method for preparing the exothermic coarse aggregate includes the following steps: Step 1: Aggregate pretreatment: Select volcanic rock crushed and ground to a particle size of 5-10 mm as raw material. Use plasma equipment at 50-100W to treat the surface of the volcanic rock for 5-10 minutes, then soak it in hydrochloric acid solution for 2-4 hours, wash it with water until neutral, and then dry it to obtain pretreated aggregate. Step 2, Iron powder loading: Immerse the pretreated aggregate in ferric chloride solution, add sodium borohydride and sodium molybdate accounting for 0.05-0.1% of the mass of ferric chloride, stir and react for 1-2 hours, then transfer to a centrifuge, centrifuge at 2000-4000 rpm for 5-10 minutes, and take the second precipitate to obtain the prepared aggregate; Step 3, salt fixation: Spray a sodium chloride-polyvinyl alcohol mixture onto the aggregate to be prepared, and dry it at 60-80℃ to obtain iron powder composite oxide aggregate, which is exothermic coarse aggregate.
5. The method for preparing high-strength permeable asphalt concrete according to claim 4, characterized in that, In step one, the concentration of hydrochloric acid solution is 5-10%, and the mass ratio of volcanic rock to hydrochloric acid solution is 1:(3-5). In step two, the concentration of ferric chloride solution is 10-20%, the mass ratio of pretreated aggregate to ferric chloride solution is 1:(2-4), and the molar ratio of ferric chloride to sodium borohydride is 1:
2. In step three, the concentration of sodium chloride in the sodium chloride-polyvinyl alcohol mixture is 5-10%, and the concentration of polyvinyl alcohol is 1-3%.
6. The method for preparing high-strength permeable asphalt concrete according to claim 2, characterized in that, In step 1, the silica sol contains 0.1-0.5% nano-titanium dioxide by total mass of silica sol.
7. The method for preparing high-strength permeable asphalt concrete according to claim 3, characterized in that, In step 3, the concentration of the silane coupling agent solution is 2-4%, and the silane coupling agent solution is prepared by mixing KH-550 and anhydrous ethanol at a volume ratio of 1:(3-5).
8. The method for preparing high-strength permeable asphalt concrete according to claim 1, characterized in that, The asphalt can be selected from any one of SBS modified asphalt, ethylene-vinyl acetate polymer modified asphalt, and styrene-butadiene rubber modified asphalt; the additive can be selected from any one of SBS, SBR, and EVA; and the solvent can be selected from any one of KH-550, KH-560, and KH-570.
9. The method for preparing high-strength permeable asphalt concrete according to claim 1, characterized in that, The mineral filler is prepared by mixing limestone powder and silica fume at a mass ratio of (2-4):
1. The limestone powder has a calcium carbonate content of ≥90% and a fineness of 200-400 mesh, and the silica fume has a silicon dioxide content of ≥90%.
10. A method for preparing high-strength permeable asphalt concrete according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Heat the coarse aggregate, fine aggregate, and exothermic coarse aggregate to 150-170℃ to obtain preheated aggregate; S2. Heat the asphalt to 160-180℃, add mineral filler, exothermic filler, additives and water, and stir at 30-80 rpm for 30-60 minutes to obtain asphalt mixture. S3. Spray the solvent evenly onto the surface of the preheated aggregate and let it stand for 10-20 minutes to obtain the prepared aggregate. S4. Add the prepared aggregate and asphalt mixture to a twin-shaft mixer and mix at a mixing speed of 30-50 rpm for 5-10 minutes to obtain the prepared material. S5. Pour the prepared material into the mold, compact it under 8-12MPa conditions, and then demold it after it cools naturally to room temperature to obtain high-strength permeable asphalt concrete.